MYOCARDIAL INFARCTION: CAUSES, SYMPTOMS, RISK FACTORS, FIRST AID. (International journal of artificial intelligence, 2025)
Myocardial infarction consists of ischemic necrosis of a specific part of the heart muscle. According to the extent of the process, two types of myocardial infarction are distinguished:transmural, andendocardial or intramural.According to the clinical course, complicated and uncomplicated myocardial infarction are distinguished. The main factors determining the clinical picture of acute myocardial infarction are the degree of damage to the coronary arteries and the development of collateral circulation; the extent of myocardial damage and its localization largely depend on these factors. According to localization, acute myocardial infarction is divided into infarction of the anterior wall, lateral wall, and posterior wall of the heart.In diagnosing acute myocardial infarction, in addition to anamnesis data, electrocardiography, enzyme diagnostics (determination of creatine kinase, aspartate aminotransferase, lactate dehydrogenase in blood serum), radioisotope diagnostics with Tc99 or Tl201, radiological diagnostics, echocardiography, selective coronary angiography, and left ventriculography are of great importance.Modern methods of treatment of acute myocardial infarction.In acute myocardial infarction, treatment should be aimed at maintaining and improving cardiac function and circulation, preventing complications, and preserving as much viable myocardium as possible. Treatment begins with relief of pain attacks and simultaneous oxygen therapy (oxygen delivery via a nasal catheter).To limit the area of myocardial damage, two groups of measures are used:measures that improve coronary perfusion of the infarct and peri-infarct zones;measures that reduce myocardial oxygen demand.Measures of the first group can be achieved through medications, endovascular (invasive), and surgical methods.